Only the Bold (The Way of Steel-Book 4) - Morgan, Rice (Lukeman Literary, 2020)
"Morgan Rice did it again! Building a strong set of characters, the author delivers another magical world. ONLY THE WORTHY is filled with intrigue, betrayals, unexpected friendship and all the good ingredients that will make you savor every turn of the pages. Packed with action, you will read this book on the edge of your seat."--Books and Movie Reviews, Roberto MattosFrom Morgan Rice, #1 Bestselling author of THE QUEST OF HEROES (a free download with over 1,000 five star reviews), comes a riveting new fantasy series.In ONLY THE BOLD, the epic finale to the Way of Steel, Royce finds him transformed after looking into the magic mirror. Has he gained the ultimate wisdom? Or has he gone mad?The mirror reveals many secrets, and Royce finds himself heading towards his father's hiding place. Will he meet his father for the first time?Genevieve and Royce's tragic romance finally comes to a head, culminating in a surprise twist that will change both of their lives forever.And amidst all of this comes the epic battle with the king's armies, one that will determine the fate of the land-and the kingship-once and for all.ONLY THE BOLD weaves an epic tale of friends and lovers, of knights and honor, of betrayal, destiny and love. A tale of valor, it draws us into a fantasy world we will fall in love with, and appeals to all ages and genders. Please visit www.morganricebooks.com for updates about the release of Morgan's forthcoming fantasy series.
Keywords: Sci-fi, fantasy; Dobrodružství, napětí, fantasy